Does corporate environmental responsibility (CER) affect corporate financial performance? Evidence from the global public construction firms. (15th September 2021) - Xu, Qian; Lu, Yujie; Lin, Han; Li, Boying
Abstract: Construction is responsible for 50% of carbon emissions, 40% of energy consumption, and half of the landfill waste globally. To confront those environmental issues, stipulating appropriate strategies to drive construction firms towards corporate environmentally responsible (CER) activities is essential. However, the impact of CER on construction firms' financial performance (FP) is still inconclusive. This study aims to investigate the relationship between CER and FP in the architecture, engineering, and construction (AEC) industry. 141 publicly listed AEC companies were selected worldwide, and the results showed that CER increased the firms' Return of Equity (ROE) and Economic Added Value (EVA) margin by 2.62% and 0.10%, respectively. Asset turnover contributed most to the increase of ROE. The spatial-temporal comparison results indicated that green listed firms' EVA margin had a promising trend while ROE fluctuated in different economic stages. The findings revealed decisive implications for AEC organizations to implement CER while maintaining the competitiveness of corporate profitability. Highlights: An assessment of CER on construction firms' profitability was provided. CER enhanced short- and long-term profitability by 2.62% and 0.10%. Increased profitability was attributed by factors including asset turnover. CER is more recognized in growth economic conditions than recessions.